One-pot, Three-Component Sulfonimidamide Synthesis exploiting the Sulfinylamine Reagent N-Sulfinyltritylamine, TrNSO - Davies, T; Hall, A; Willis, M (Wiley, 2017)
Sulfonimidamides are increasingly important molecules in medicinal chemistry and agrochemistry, but their preparation requires lengthy synthetic sequences, which has likely limited their use. We describe a one‐pot de novo synthesis of sulfonimidamides from widely available organometallic reagents and amines. This convenient and efficient process uses a stable sulfinylamine reagent, N‐sulfinyltritylamine (TrNSO), available in one step on 10 gram scale, as a linchpin. In contrast to classical approaches starting from thiols or their derivatives, our TrNSO‐based approach facilitates the rapid assembly of the three reaction components into a variety of differentially substituted sulfonimidamides containing medicinally relevant moieties, including pyridines and indoles. Analogues of the sulfonamide‐containing COX‐2 inhibitor Celecoxib were prepared and evaluated.